Structural aspects of plant antimicrobial peptides. - Padovan, Lara; Scocchi, Marco; Tossi, Alessandro (Curr Protein Pept Sci, 2010)
Antimicrobial peptides exert an important role in plant defence and their structure/activity relationship against pathogens is widely described. Although the most striking feature of these antimicrobial peptides is their molecular diversity, they share some common features, such as a relatively low molecular weight, and the presence of a variable number of cysteines residues that contribute to stabilize conserved scaffolds through disulphide bond formation, and can be assigned to different structural classes. Peptides from different classes in some cases act synergistically against pathogens when produced by the same tissue, and contribute to extending defence to a wider range of microbes. In this review we briefly describe the structure of some of the main plant antimicrobial peptide classes: thionins, defensins, lipid transfer proteins, cyclotides and snakins, and how they are reported to contribute to the plant protection. In many cases these antimicrobial peptides show a wider activity spectrum than that suggested by their name, exerting an action also against predatory insects and revealing useful antiviral activities. This extends their interest from defense of important food crops also to the design of novel anti-infective compounds for both pharmaceutical and agricultural applications.
Keywords: Amino Acid Sequence; Antimicrobial Cationic Peptides; Molecular Sequence Data; Plant Proteins; Plants; Sequence Alignment